2010
DOI: 10.1016/j.chembiol.2010.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Profiling Reveals Reactivity of the Murine Thymoproteasome-Specific Subunit β5t

Abstract: SUMMARY Epithelial cells of the thymus cortex express a unique proteasome particle involved in positive T cell selection. This thymoproteasome contains the recently discovered β5t subunit that has an uncharted activity, if any. We synthesized fluorescent epoxomicin probes that were used in a chemical proteomics approach, entailing activity-based profiling, affinity purification, and LC-MS identification, to demonstrate that the β5t subunit is catalytically active in the murine thymus. A panel of established pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 26 publications
1
82
0
Order By: Relevance
“…Expression of thymoproteasomes by cortical TECs is essential for positive selection of most, although not all, CD8 thymocytes (27). Because of their low chymotrypsin-like activity, thymoproteasomes are predicted to generate peptides that bind MHC I molecules with low affinity and, therefore, yield unstable MHCpeptide complexes (59,63). It would seem plausible that being more stable, thymoproteasome-independent MHCI-peptide complexes would elicit stronger TCR signals.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of thymoproteasomes by cortical TECs is essential for positive selection of most, although not all, CD8 thymocytes (27). Because of their low chymotrypsin-like activity, thymoproteasomes are predicted to generate peptides that bind MHC I molecules with low affinity and, therefore, yield unstable MHCpeptide complexes (59,63). It would seem plausible that being more stable, thymoproteasome-independent MHCI-peptide complexes would elicit stronger TCR signals.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the ABPs signal in adherent C2C12 cells confirmed that the MVB127 signal in cells was not reduced in Epox‐treated cells (Figure 4C). The MVB127 non‐specific signal was mostly localized to membrane structures because of its lipophilic property 18. The LW124 non‐specific signal was found in the nucleus (Figure 4C).…”
Section: Resultsmentioning
confidence: 98%
“…We recently reported that in the C2C12 cell culture, β5 protein levels are lower than β2;14 this indicates that β5 activity in C2C12 is higher than β2 activity. Also, in mouse thymus, the β5 signal is higher compared with the other subunits 18. Thus, specific proteasomal activity in cells and tissues should include subunit‐specific analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was performed as previously reported. [42] Peptides were desalted on stage tips [43] and analyzed with a trap-elute system on C18 reversed phase nano LC with a 45 min 10-60% ACN/0.1% formic acid gradient, hyphenated to a Thermo LTQ-orbitrap mass spectrometer using a top 3 data dependent protocol at 60.000 resolution, m/z range 300-2000, 1000 msec fill time in the Orbitrap, for MS/MS fragmentation 35 units of CID energy, 120 msec max fill time, AGC 50 e3 and a threshold of 750 counts. Ions of z = 2+ and higher were selected to be fragmented twice within 10 sec prior to exclusion for 150 sec.…”
Section: Proteomicsmentioning
confidence: 99%